2014
DOI: 10.1523/jneurosci.2264-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Role for the Cerebellum in Encoding Internal Models: Evidence from Semantic Processing

Abstract: The striking homogeneity of cerebellar microanatomy is strongly suggestive of a corresponding uniformity of function. Consequently, theoretical models of the cerebellum's role in motor control should offer important clues regarding cerebellar contributions to cognition. One such influential theory holds that the cerebellum encodes internal models, neural representations of the context-specific dynamic properties of an object, to facilitate predictive control when manipulating the object. The present study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 59 publications
16
116
0
Order By: Relevance
“…Furthermore, the role of cortico-cerebellar circuits seems to be out of question with respect to speech motor control. However, there is increasing evidence that the cerebellum also contributes to top-down mechanisms during speech perception by serving predictive functions (Moberget et al, 2014). In this respect, the SMA seems to play a coordinative role between procedural memory traces, on the one hand and cognitive structures such as syntax and grammar, on the other (Ullman, 2004).…”
Section: Sma and Pre-sma As An Interface Between Procedural And Declamentioning
confidence: 99%
“…Furthermore, the role of cortico-cerebellar circuits seems to be out of question with respect to speech motor control. However, there is increasing evidence that the cerebellum also contributes to top-down mechanisms during speech perception by serving predictive functions (Moberget et al, 2014). In this respect, the SMA seems to play a coordinative role between procedural memory traces, on the one hand and cognitive structures such as syntax and grammar, on the other (Ullman, 2004).…”
Section: Sma and Pre-sma As An Interface Between Procedural And Declamentioning
confidence: 99%
“…This hypothesis is based on many studies that have found cerebellar involvement in more cognitive tasks [27] and the uniform microanatomy throughout the cerebellum that suggest similar computations in both motor and cognitive domains [28]. Probably more relevant to sequence learning and generalization, the cerebellum is involved in cognitive functions such as applying rules that constrain responses [29] and language [30].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this hypothesis, in a recent fMRI study using healthy young controls, the BOLD response in lateral posterior cerebellum to the final word of a sentence was stronger when the sentence established a strong semantic expectancy, compared to when the final word was not predictable (Moberget, Gullesen, Andersson, Ivry, & Endestad, 2014). Especially pronounced activations were observed when the final word violated the semantic prediction, consistent with the hypothesis of error-based learning in the cerebellum (Doya, 1999; Ito, 2006; Ramnani, 2006).…”
Section: Introductionmentioning
confidence: 58%
“…The data for nine of these participants were included in our original report (Moberget et al, 2014). Control participants were self-reported as right-handed and reported no neurological or current psychiatric problems.…”
Section: Methodsmentioning
confidence: 99%